The use of urethral bulking injections in post‐prostatectomy stress urinary incontinence: A narrative review of the literature. Issue 8 (20th August 2019) - Nguyen, Linh; Leung, Lap Yan; Walker, Roger; Nitkunan, Tharani; Sharma, Davendra; Seth, Jai
Abstract: Aims: Post‐prostatectomy stress urinary incontinence (PPI) is a common condition with significant impact on patient quality of life. With rising numbers of prostatectomies performed, recognition of incontinence during survivorship care is growing. With increasing hesitance of the use of suburethral mesh in females, urethral bulking injections in this patient population as a minimally invasive alternative to surgery are evaluated. This review aims to evaluate the existing evidence base for urethral bulking therapy in PPI and provide a summary of its efficacy, durability, and side‐effect profile. Methods: A literature search of Medline/Pubmed and Cochrane databases was conducted to identify publications reporting the clinical outcomes of urethral bulking injections in patients with PPI, up to and including October 1st, 2018. Case reports, letters and reviews were excluded. Results: We identified 25 studies that fit our inclusion criteria, comprised of one RCT, two large retrospective cohort studies, and 22 case series. The success rates reported varying widely from 13%‐100% with reports of symptomatic control deterioration. Complication rates remain low. This review highlighted a poor performance using the more historic bulking agents (BA), and the lack of strong evidence with the more novel BA in PPI and discussed challenges regarding optimal patient selection and techniques. Conclusions: There exists poor clinical evidence base concerning the use of urethral bulking in PPI with few high‐level studies and a significant lack of consistency between studies. Further study in this area is required to evaluate the role of BA in this patient population.